Empirical Essays in the Economics of Ageing and the Economics of Innovation - Janina Reinkowski (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2013)
This dissertation consists of five distinct empirical papers covering two large areas of research that are rather independent from each other: the economics of ageing and the economics of innovation. The first three chapters cover the impact of intergeneration interaction on the parents of adult children. Chapter 1 explores the effects of grandchild care on grandparent labour supply. Chapter 2 on the other hand investigates the impact of grandchild care on grandparent health. Chapter 3 analyses the effect of a divorce of an adult child on the parent. The final two chapters take another direction. They evaluate the effects of research and development (R&D) promoting subsidy schemes. Chapter 4 looks at two regionally focused subsidies in the German biotech sector, while Chapter 5 investigates the effect of R&D subsidies from multiple national and international sources on small and medium sized enterprises (SME) in Thuringia.
Keywords: I10; J13; J14; C14; C21; O32; O38; 330; Employment; Ageing; Grandparental health; Grandchild care; R&D subsidies; East Germany; SME; Cluster-policy; Biotech; Causality.; Ältere Menschen; Eltern; Kinderbetreuung; Arbeitsangebot; Scheidung; Gesundheit; Schätzung; Deutschland; Technologiepolitik; Regionales Cluster; Biotechnologie; Deutschland; Forschungsfinanzierung; Betriebsgröße; Wirkungsanalyse; Schätzung; Ostdeutschland